Production, purification, and characterization of a thermally stable, Acidophilic Cellulase from Aspergillus awamori AFE1 isolated from Longhorn beetle (Cerambycidae latreille) - Ayoola E. Afe; Olusola T. Lawal; Olufemi S. Bamidele; Farhad Badshah; Bukola R. Oyelere; Andrew N. Efomah; Mostafa A. Abdel-Maksoud; Sabiha Fatima; Abdulaziz Alamri; Mohamed A. El-Tayeb; David M. Sanni (Microbial Cell Factories)
Abstract Background The relentless pursuit of cost-effective cellulase, a key enzyme in the biocatalytic conversion of cellulose, has led to exploring insect guts as potential sources of biocatalysts. Herbivorous insects’ intestinal tracts are recognized as rich reservoirs of cellulolytic microorganisms. This study investigates cellulase production, purification, and characterization from Aspergillus awamori AFE1, isolated from the gut of longhorn beetles (Cerambycidae latreille). Basic cellulase production parameters were optimized. The cellulase produced under optimum conditions was purified by ammonium sulphate precipitation and chromatographic methods, followed by characterization of the purified enzyme. Results Optimum cellulase production was observed at pH 5 and 30 °C, using cellulose and NaNO3 as carbon and nitrogen sources. Cellulase was purified to homogeneity, with a molecular weight of 48.5 kDa. The cellulase exhibited optimal activity at pH 5.0 and maintained stability at an acidic pH of 4.0, showing 80% activity after 2 h and 40% activity remaining after 6 h. The optimal temperature for cellulase activity was 60 °C, with maximal stability at 30 °C, retaining 63% of its initial activity after 2 h. However, significant activity of 50% was noted at 50 °C for 2 h. Interestingly, the enzyme showed great stability against organic solvents up to 4 h and retained significant enzymatic activity after 5 h. Cellulase activity was also enhanced by divalent metal ions, Fe2+ and Zn2+, but was markedly inhibited by urea and EDTA, and monovalent Na+, K+, including some divalent metal ions, Cu2+ and Mn2+. It displayed Km and Vmax values of 3.86 mM and 0.3159 mg/mL/min, respectively. Conclusion This study has shown Aspergillus awamori AFE1, isolated from the Longhorn beetle gut, as a unique source of acid-stable, thermostable, and organic solvent-resistant cellulase with industrial potential. Its unique enzymatic properties offer promising applications in biofuel production and lignocellulosic biomass conversion.